LOCAL WISDOM AS A CULTURAL ENGINE OF INTERFAITH HARMONY: STRENGTHENING RELIGIOUS MODERATION AND MITIGATING RACISM IN TANA TORAJA - Nawir, Muhammad; Mukramin, Sam'un; Ismail, Lukman; Asnawi, Mu’aliyah Hi; Nursida, Andi; Abu Bakar, Noor Insyiraah (Harmoni, 2025)
The issue of racism and racial discrimination requires deeper exploration, as these phenomena continue to persist as global concers that are highly sensitive and resistant to resolution. Racism often triggers escalating social tensions and conflicts that significantly affect interreligious relations, even though such problems do not always originate from religious differences. In this regard, an approach that integrates religious moderation with local wisdom is considered vital in establishing sustainable social harmony. Local wisdom serves as a bridge that connects cultural values and spirituality within a pluralistic society, fostering mutual respect and tolerance among people of different faiths particularly in the context of Islam and Christian relations. However, the role of local wisdom in facilitating religious moderation across diverse racial backgrounds remains underexplored. Therefore, this study aim to fill the gap. The research employs in depth observation and interviews as data collection methods, with Tana Toraja selected as the research site due to its well known cultural pluralism and strong religious identity. The primary informants consist of religious leaders, traditional elders, community leaders, and practitioners who play crucial roles in maintaining social and cultural cohesion. The findings reveal that: 1) the Torajan people are able to preserve and respect their religious traditions while remaining open to external influences and societal change; 2) the integration of local wisdom into religious moderation in Toraja holds significant potential for fostering harmony among religious communities while preserving valuable cultural traditions; and 3) the prevention of racism through the application of local wisdom emphasizes the importance of understanding, respecting, and promoting local cultural values and customs particularly through the developments of the tourism industry as a new platform of interreligious appreciation, dialogue, and cultural coexistence.